Improvement of Water Saturation and Formation Factor Parameters in a Clastic Reservoir, Zagros Basin, SW Iran - Bahman Soleimani; Mohamad Hassani Giv (Journal of Chemical and Petroleum Engineering, 2016)
Water saturation (Sw) is one of the most important petro-physical parameter for evaluating the clastic horizons of hydrocarbon reservoir, which can be calculated using Archie's equation. The Archie's parameters (m, a) are the major source of uncertainty in the calculation of Sw. In order to obtain Archie's parameters, a total number of 117 sandstone samples, having resistivity measurements from Asmari Formation were studied. Due to scattered data points on the Log-Log plot of F versus Ø and to obtain reliable values for m and a parameters, the data were classified based on current zone indicator (CZI) into 6 classes of electrical flow unit (EFU). The values of parameters m and a obtained from F-Ø cross plots with excellent correlation coefficient. To avoid from data diversity and to make data applicable, the average values of m and a were obtained with considering the number of samples in each class. To assess the validation of the calculated F based on proposed values of m and a, the measured values of F versus calculated one's using Archie, Tixier and Humble formulas and proposed values were compared. The plot shows that the calculated F using Archie Tixier and Humble formulas are lower than calculated F using proposed and measured values. Applying the determined values seems to reasonably minimize the error in calculating F and therefore Sw%.